Fiscal Reaction Functions in the CFA Zone : An Analytical Perspective - Williams, Oral (IMF Working Papers; Working Paper, 2007)
The stance of fiscal policy in CEMAC and WAEMU is strongly influenced by fiscal effort in the previous period. This persistence underscores the risks of a procyclical fiscal policy stance, given these countries' high degree of dependence on primary commodities and exposure to terms of trade shocks. This paper finds that the coefficient of the lagged debt stock was significant and positive, consistent with the theory that higher levels of debt warrant greater fiscal effort. Various measures of economic performance, as captured by economic growth and per capita GDP, openness, and the terms of trade were also found to be important factors in explaining fiscal performance. As fiscal performance seems to be strongly affected by both real GDP growth and terms of trade fluctuations, there appears to be a need to develop supplementary fiscal-related criteria that take into account the influence of output and the terms of trade.